AB0441 Evaluation of nailfoldvideocapillaroscopy in behçet's disease. (23rd January 2014) - Balkarli, A.; Özkan, Ü.; Temel, S.; Ozhan, N.; Cobankara, V.
Abstract : Background: Behçet's disease is a systemic vasculitis with the involvement of all kinds of veins and arteries and is characterized by repeating mucocutaneus and ocular involvement. Objectives: We aimed to determine microvascular abnormalities in Behçet patients with nailfoldvideocapillaroscopy. Methods: We included 82 patients who were diagnosed with Behçet's disease according to international diagnosis criteria. Patients were reviewed about smoking, Raynaud's phenomena and ischemic ulcers. Patients who had comorbidities including hypertension, smoking and Raynaud's phenomena were not included in this study. As a control group we enrolled 30 healthy individuals matched for age and sex and who were not smoking. We used videocapillaroscope (x200) for capillaroscopic evaluation. Patients were put to hand rest (protection from trauma) 2 weeks before the capillaroscopic procedure and hands were held in room temperature at least 20 minutes on the day of the procedure. Immersion oil was used for better evaluation. 8 fingers excluding thumbs were evaluated independently by 2 doctors, and signs were recorded to patient follow-up form. We evaluated capillary quantity, microhemorrhage, ectasied capillaries (neat-not neat), megacapillaries, avascular space, bushy capillaries, meandering capillaries, neovascularization and bizarre capillaries with nailfoldvideocapillaroscopy. Ectasied capillaries were defined as capillary diameter >0.02 nm, megacapillaries as >0.05 nm, and microhemorrhage was defined as hemorrhage determined in at least two fingers without trauma. Results: Mean age for patients was 36.9±11.8 (17-63), disease starting age was 29.8±9.7 (14-60), disease duration was 7±8.3 years. Capillary quantity within one millimeter space was 10.17±1.235 (9-13). We determined megacapillary in two (2.4%), microhemorrage in 4 (4.9%), tortuosity in 75 (91.5%) and bizarre capillary in 8 (9.8%) patients. No pathological signs were observed in the control group. No association was found between capillaryscopic pathologies and age, disease starting age, disease duration and clinical signs. Tortuosity was more frequents in patients who had pulmonary artery involvement (6.6% vs 33%); however, the difference was not significant. Conclusions: We found less specific capillaroscopic pathologies in our study when compared with other studies. The reason for that can be our patient choice as we did not include patients with hypertension, smoking and Raynaud's phenomena. Pathologies we detected might originate from vasculitic nature of Bahçet's disease. Further studies are needed to clarify the diagnostic and prognostic value of capillaroscopy in BD. Disclosure of Interest: None Declared